Substrate-dependent oxidative inactivation of a W-dependent formate dehydrogenase involving selenocysteine displacement - Vilela-Alves, Guilherme (2024)
Funding Information: This work was financially supported by Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia (FCT, Portugal) through fellowship no. 2023.00286.BD (G. V.-A.) and DFA/BD/7897/2020 (R. R. M.), grant no. PTDC/BII-BBF/2050/2020 (http://doi.org/10.54499/PTDC/BII-BBF/2050/2020) (I. A. C. P. and M. J. R.), research contract 2020.00043.CEECIND (A. V.) and R&D units MOSTMICRO-ITQB (grant no. UIDB/04612/2020 and UIDP/04612/2020) (I. A. C. P.) and UCIBIO (grant no. UIDP/04378/2020 and UIDB/04378/2020) (M. J. R.), and Associated Laboratories LS4FUTURE (grant no. LA/P/0087/2020) (I. A. C. P.) and i4HB (grant no. LA/P/0140/2020) (M. J. R.). The NMR spectrometers at FCT-NOVA are part of Rede Nacional de RMN (PTNMR), supported by FCT-MCTES (ROTEIRO/0031/2013-PINFRA/22161/2016) (cofinanced by FEDER through COMPETE 2020, POCI and PORL and FCT through PIDDAC). This work was also funded by the French national research agency (ANR \u2013 MOLYERE project, grant no. 16-CE-29- 0010-01) (B. G.). We thank Prof Carlos Rom\u00E3o for insightful discussions pertaining the coordination chemistry of the SeCys unbound active site and the excellent technical assistance of Jo\u00E3o Carita from ITQB NOVA on microbial cell growth. We thank the reviewers for their constructive comments that significantly enhanced the manuscript. We are also grateful to the EPR-MRS facilities of the Aix-Marseille University EPR centre and acknowledge the support of the European research infrastructure MOSBRI (grant no. 101004806) (B. G.) and the French research infrastructure INFRANALYTICS (MOLYERE, 16-CE-29-0010-01) (B. G.). This work was supported by the computing facilities of the CRCMM, \u201CCentre R\u00E9gional de Comp\u00E9tences en Mod\u00E9lisation Mol\u00E9culaire de Marseille\u201D. We also acknowledge the ESRF Synchrotron for provision of synchrotron radiation facilities, and we thank the staff of the ESRF and EMBL Grenoble for assistance and support in using the HPMX lab and beamlines ID23-1, ID30A-3, ID30B. Publisher Copyright: © 2024 The Royal Society of Chemistry.